The Urgency of Legal Protections for Corporate Entities in Bank Credit Applications Based on Electronic Land Certificates - Al-Ghiffari, Fakhruddin; Gultom, Elisatris (Journal of Law, Politic and Humanities, 2025)
The Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency (Permen ATR/BPN) Number 3 of 2023 on the Issuance of Electronic Documents in Land Registration was enacted by the government to improve the quality of public services related to land registration activities while also providing protection for citizens' data regarding land rights. This regulation serves as the legal foundation for the use of electronic systems in land registration processes, the use of electronic documents during land registration, the utilization of electronically converted documents, and the legal recognition of electronic land certificates. One of the highlights of this regulation is the implementation of electronic land certificates for land rights holders. According to Article 1 point 9 of Permen ATR/BPN Number. 3 of 2023, an electronic land certificate is defined as a certificate issued through an electronic system, formatted as an electronic document, and stored in electronic land registers. Based on this description, it can be understood that the electronic land certificate represents the government's commitment to optimizing the use of information technology in services related to land ownership rights. Through the adoption of information technology, it is expected that risks associated with physical document damage and theft can be minimized, ease of access for land rights holders can be enhanced, and the issuance process of land certificates can be expedited. In addition to discussing the benefits of electronic land certificates, this paper also examines the legal protection afforded to legal entities as holders of land rights, particularly corporations. Corporations are the central focus of this journal, as land certificates are among the most common and widely used collateral objects for bank credit facilities